Identificação de borboletas (Lepidoptera) da coleção entomológica da Universidade Federal do Norte do Tocantins - OLIVEIRA, Rossana Carreiro Lima (Universidade Federal do Tocantins, 2023)
The identification and cataloging of butterfly species is very necessary, as it is only by knowing the biodiversity that this fauna can be preserved for future generations. Thus, the present work aimed to identify and catalog the butterfly species present in the Entomological Collection of the Federal University of the North of Tocantins (UFNT) in order to facilitate the knowledge about the occurrence data distribution of the invertebrate species and in the city of Araguaína-TO and region. Species were identified using a specialized bibliography and all butterflies were photographed in dorsal and ventral views. In all, 17 species of butterflies were identified, distributed in four families: Hesperiidae, Nymphalidae, Papilionidae and Pieridae